2017
DOI: 10.15713/ins.jcri.164
|View full text |Cite
|
Sign up to set email alerts
|

Use of dental anxiety questionnaire and clinical approaches: A National survey among pediatric dentists in India

Abstract: Background:The intensity and nature of dental anxiety varies between individuals. Dental anxiety has been documented as a cause of grave health issues in children and if continued till their adolescence, will lead to unsettling behavior while treatment. Hence, it is essential to recognize a dentally anxious child at the earliest using dental anxiety assessment indices. Hence, the study was planned to evaluate the use of dental anxiety assessment questionnaire and clinical approaches among pediatric dentist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In our study the prevalence of anxious patients was quite high ranging to a maximum of 85 % when we calculated the anxiety levels between various groups we found that most of the young patients (below 30 years) (70%) were more anxious to dental treatment than the older age groups (30%), which can be explained on the fact that high percentage of young patients are usually more apprehensive. 7 Other researches which support this fact say that anxiety might decrease with age include the ability to cope with experiences or the phenomenon may be due to the ageing process itself characterized by a general decline in anxiety. 8,9 When gender was compared we found a relation between the gender of the patient and anxiety.…”
Section: Discussionmentioning
confidence: 97%
“…In our study the prevalence of anxious patients was quite high ranging to a maximum of 85 % when we calculated the anxiety levels between various groups we found that most of the young patients (below 30 years) (70%) were more anxious to dental treatment than the older age groups (30%), which can be explained on the fact that high percentage of young patients are usually more apprehensive. 7 Other researches which support this fact say that anxiety might decrease with age include the ability to cope with experiences or the phenomenon may be due to the ageing process itself characterized by a general decline in anxiety. 8,9 When gender was compared we found a relation between the gender of the patient and anxiety.…”
Section: Discussionmentioning
confidence: 97%